Application of children’s fiction narrative writing genre among slow learning children - Yaakob, Nor Azuwan; Sariyan, Awang; Syed Abdullah, Syed Nurulakla; Sha'ri, Sharil Nizam; Bouville, Audrey Geraldine (Human Resource Management Academic Research Society, 2021)
This study focuses on the application of fiction writing techniques of children's stories among students who are slow learners, in a selected primary school in Malaysia. The objectives of the study are: to identify the application of fiction genre writing of children's stories among slow learners; to analyse the important categories of language elements in fiction writing applied in writing; and to summarise the achievement of slow learners in fiction writing of children’s stories. Essays by the students were analysed based on two main categories of language in fiction writing: linguistic and stylistic aspects. The linguistic aspect studies the mechanical elements of language, while the stylistic aspect looks at the style of language. For this study, two categories of the linguistic aspect were analysed: lexical category and syntactic category. The lexical category focuses on morphology (word construction and word class), while the syntactic category studies the basic structure of sentences, consisting of subject-predicate, sentence complexity (basic sentence and compound sentences), sentence types (statement sentences, question sentences, request sentences, and exclamation sentences), as well as sentence variety (active and passive sentences). For the stylistic aspect, the categories analysed were diction in terms of expressions of utterances and proverbs, as well as context and coherence. Data analysis was carried out using the Leech and Short (2007) model modified for fiction in Malay literature (Sariyan, 2013). The findings show that first, there were some items in the field of linguistics that were not or were less mastered by the respondents. However, there were some items that were achieved satisfactorily. Second, in the field of stylistics, respondents were not able to apply the items studied, especially diction in expressions of utterances and proverbs. As for the context and coherence items, a number of respondents achieved a relatively high level of application.